Britain's authoritarian turn. (April 2021) - Webber, Frances
Looking back, in December 2020, at the year since Boris Johnson's Conservatives were swept back into government with a huge majority, the author identifies a raft of new laws, Home Office measures and government proposals in the fields of policing, crime, and immigration and asylum which embody long-held rightwing projects. Coming on top of already discriminatory practices, these include restrictions on the fundamental right of peaceful protest and freedom from invasive and racist policing, the subjection of migrants and asylum seekers to dangerous and inhumane conditions and the removal of legal protections for asylum seekers. Simultaneously, Bills going through parliament restrict or remove altogether the legal accountability of state actors, including soldiers on overseas operations and police informants, for crimes including torture and murder. Citizens' recourse to the courts to challenge unlawful ministerial decisions is also under threat.